The use of information technology and its influence on Accounting education quality – A study of staff members King Khalid University – - Musa, Amna Gibreel Abunsibb (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to investigate the relationship between use of information technology dimensions (databases, networks, physical components, and communications) and Accounting education quality at King Khalid University in the Kingdom of Saudi Arabia. The model was built and development of hypotheses and measurements based on the literature review of the previous studies the study used the method of comprehensive inventory to collect data through the questionnaire. 62 questionnaires were analyzed. for the analysis of data and hypotheses testing, a descriptive statistical method was used (frequencies, percentages, deviations,) and analytical statistical methods (Exploratory Factor Analysis, Confirmatory Factor Analysis, Pearson correlation and path analysis) through the statistical package for social sciences (SPSS) program. The results found that a partial relationship between use of information technology dimensions and technical efficiency, existence a partial relationship between use of information technology dimensions and the professional skills quality, the results indicate that The use of information technology partly influence the ethical values quality. The study recommended that the need to enhance use of information technology in accounting education at King Khalid University in order to raise the level of performance of accounting graduates. The need to highlight the importance of information technology in the accounting profession through activating it through conferences, lectures, seminars, scientific research and training courses.